If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4u + -12 = 36 Reorder the terms: -12 + 4u = 36 Solving -12 + 4u = 36 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 4u = 36 + 12 Combine like terms: -12 + 12 = 0 0 + 4u = 36 + 12 4u = 36 + 12 Combine like terms: 36 + 12 = 48 4u = 48 Divide each side by '4'. u = 12 Simplifying u = 12
| -4y1/3 | | Q+15=34 | | p(r)=r^2-0.1/144 | | 10x+6=7x-8 | | x^2=-7-8 | | 11+9x=2x-3 | | 47=4u-17 | | 27-2x=9 | | 7*6-12=5x+m | | 10s-40=-94 | | y(2y-5)=12 | | a*(t+z)=45*z+67 | | 6m+54=17 | | 9b-2= | | -c-4=1 | | g(r)=8r+4 | | 7+22=133 | | 4(-x+2)+3(x-1)=0 | | (2w+7x+5)(3w-5x)= | | x-3/5+2x=0 | | 5(x+1)=4(x-7) | | -5(3t-2)+2t=4t-3 | | 5(x+1)=(x-7) | | x(3x+2)+x(x+6)=7+x(4x+1) | | 12x+4=7x-30+4 | | 5+2(x+3)=10 | | 30x-4x=12-7x | | 7e^3x+2=27 | | 16x+y=80 | | X-(16/x)=6 | | 2x-(x-5)+3(x-1)=12 | | (6n^2-5n^3)+(n^3+5n^2)=0 |